Pleiotropic Effects of Simvastatin on the Regulation of Potassium Channels in Monocytes - Wang, Shaoping; Ran, Yuhua; Chen, Xuejun; Li, Chungang; Cheng, Shujuan; Liu, Jinghua (Frontiers in Pharmacology, 2020)
The underlying mechanism of pleiotropic effects of statins on atherosclerosis is still unclear. Kv1.3 and KCa3.1 are two potassium channels which might be involved in monocyte migration and atherosclerosis formation. The aim of this study was to investigate the effect of simvastatin on the Kv1.3 and KCa3.1 in monocyte.In human monocytic THP-1 cells, simvastatin significantly inhibited Kv1.3 mRNA and proteins expression by real-time quantitative PCR analysis and western blotting. However, simvastatin had no effects on KCa3.1 mRNA and proteins expression. By whole-cell patch clamp, simvastatin (10 μM) remarkably inhibited the current intensity of Kv1.3, but had no effect on KCa3.1. Simvastatin (10 μM) treatment significantly reduced the monocyte chemoattractant protein 1 (MCP-1)-induced monocyte migration. This inhibition was only partially reversed by mevalonate (1mM). In human peripheral blood mononuclear cells (PBMCs), both Kv1.3 and KCa3.1 mRNA expression were increased in patients with coronary artery diseases (CAD) (n = 20) compared to healthy controls (n = 22). However, simvastatin (40 mg per day) significantly inhibited the Kv1.3 but not KCa3.1 mRNA expression after 1 month and 3 months therapy in CAD patients.Our data suggested Kv1.3 in monocytes was a potential molecular target of the pleiotropic effects of statins. KCa3.1 might be another marker of CAD, but not associated with statins treatment.